Oxidative Stress after a Carbohydrate Meal Contributes to the Deterioration of Diastolic Cardiac Function in Nonhypertensive Insulin-treated Patients with Moderately Well Controlled Type 2 Diabetes - von Bibra, H.; St John Sutton, M.; Schuster, T.; Ceriello, A.; Siegmund, T.; Schumm-Draeger, P.-M. (Hormone and Metabolic Research, 2013)
The prevalence and prognostic importance of diastolic dysfunction in type 2 diabetes has only recently been appreciated. We tested the hypothesis that in insulin treated type 2 diabetes (D), carbohydrate consumption induces oxidative stress resulting in further impairment of diastolic function beyond structural myocardial stiffness. The effects of a pure carbohydrate breakfast (48 g) on oxidative stress and cardiac function were studied in the fasting and postmeal states in subjects without hypertension or overt cardiac disease (moderately well controlled D, n=21 and controls without D, n=20). Studied variables included systolic and early diastolic (E′) myocardial velocities, traditional metabolic and hemodynamic parameters, serum nitrotyrosine, and sVCAM-1. In D compared to control subjects, the postmeal increase (∆) in glucose (1.44±2.78 vs. 0.11±0.72 mmol/l, p=0.04) and ∆nitrotyrosine (0.34±0.37 vs.  − 0.23±0.47 nM/l, p<0.001) were significantly higher. sVCAM-1 was higher in fasting and postmeal (p=0.02). E′ was significantly lower in postmeal (7.3±1.3 vs. 9.6±1.3 cm/s, p<0.001) and fasting (p<0.001) whereas the rate pressure product was significantly higher (9 420±1 118 vs. 7 705±1 871 mm Hg/min, p<0.001). Multivariable regression models of the pooled data demonstrated that independent predictors for postmeal E′ were ∆nitrotyrosine and septal thickness (R2 0.466) and for fasting E′ age, ∆nitrotyrosine, and septal thickness (R2 0.400). In insulin requiring type 2 diabetes, carbohydrate consumption may induce oxidative stress that is associated with worsening diastolic function, indicating that this metabolic factor is an important determinant of diastolic dysfunction in the diabetic heart beyond the increase in structural myocardial stiffness.
Keywords: diastolic function; type 2 diabetes; oxidative stress; postmeal hyperglycemia; tissue Doppler